Implementation of TQM in Manufacturing Industries of Developing Countries - Case Study: Albanian Companies (European Journal of Formal Sciences and Engineering, 2025)
Manufacturing industry in Albania has been grown significantly over the last decades due to increased public demand, Government’s initiatives, and the investors increased interest in the manufacturing sector. Unfortunately, quality of product is still an important issue for the locally produced goods. Only a few manufacturers are producing high quality products with higher customer satisfaction. Many of them are holding quality certificates but a few has reached a stage of product development where they are able to apply modern quality principles and techniques effectively. Research on product quality improvement shows that meeting customer satisfaction, increasing profits and reducing losses to a minimum level can be attained through the application of modern quality philosophies and principles such as Total Quality Management (TQM). Understanding the tools and techniques of TQM is considered to be significant in order to get useful results. A better understanding is required to investigate the current status of TQM implementation. This research article presents a survey on current quality control practices within the manufacturing industries in Albania to assess the potentiality of implementing TQM technique and principles in order to improve the customer satisfactions and market share.
Keywords: Quality, Total Quality Management, Albanian Manufacturing Industry